3D computer model of the Co-Cu-CoS-Cu2S subsystem T-x-y diagram above 800oC (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The three-dimensional computer model of the Co-Cu-CoS-Cu2S subsystem T-x-y diagram at temperatures above 800oC is represented. It is shown that the liquid immiscibility in the binary subsystem Cu-Cu2S is transformed within the ternary system with Co into the wide two-phase region of two immiscible melts, which interrupts the univariant curve of the Co and Cu2S co-crystallization. The special features of the structure of the solidus surface of cobalt, caused by liquid-phase immiscibility are considered.
Keywords: Phase diagrams; Immiscibility; 3D visualization; Metal-sulfide systems; Alloys of cobalt and copper